Cognitive processes underlying tactical judgment when executing a pass in soccer - Natsuhara, T.; Nakayama, M.; Kato, T.; Nagano, T.; Yoshida, T.; Sasaki, R.; Asai, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2015)
Some of the mechanisms underlying superior performance in sports may be clarified by investigating the role of visual information in the execution of particular responses by expert athletes. The aim of this study was to examine how soccer players process visual information when executing a tactical pass in a 4 vs. 4 attacking play scenario. To identify the cognitive processes operating during task execution, we measured eye movement and correlated it with verbal reports from players. The subjects comprised 30 soccer players with differing proficiencies (15 "experts" and 15 "sub-experts"). Two tests were carried out: a test to evaluate the level of passing skill, and a decision-making test to evaluate the reproducibility of tactical passing and the accuracy of passes aimed to specific locations. Eye movements were measured during the decision-making test. Furthermore, in each trial of the decision-making test, verbal reports were collected. These related to how and why participants decided to pass the ball to any particular player among the four attackers on screen and, in order to determine their best judgment, how they captured the play situation and what they paid attention to. The results revealed that for execution of the pass, the experts were significantly more proficient at passing accurately to the aimed location, and their passing judgment was more reproducible in comparison to the sub-experts, although both groups had a uniform level of passing skill in terms of pass execution. In addition, eye movement data obtained during pass execution confirmed that in the play observation phase, while experts maintained their line of sight on other objects, they also maintained a longer gaze on defensive players to identify gaps between them. Also in the ball approach phase, the experts maintained a longer gaze on the player who was judged to be the best choice for receiving an accurate pass. These observations suggest that the superior passing performance of expert soccer players is attributable to accurate and efficient extraction of visual information and utilizing it in the context of their accumulated knowledge base.